A Rare Cause of Abdominal Pain and Fever of Unknown Origin: Takayasu Arteritis - Özlem Üzüm; Muhammed Ali Kanık; Kader Vardı; Yeliz Pekçevik; Kayı Eliaçık; Belde Kasap Demir (Galenos Publishing House, 2019)
Fever of unknown origin has three most common etiologic categories in children; infectious diseases, connective tissue diseases, and neoplasms. Takayasu arteritis is a chronic vasculitis involving the large vessels, which generally presents with clinical features of vascular sequelae such as abdominal pain, hypertension, headaches and fever. In this article, we presented a 11 year-old girl admitted with fever lasting for one month and abdominal pain. Her physical examination and biochemical parameters were all in normal limits except for fever, abdominal pain and elevated acute phase reactant. Exclusion of infectious diseases, neoplasms and juvenile idiopatic arthritis, systemic lupus erythematosus; and demonstration of increased wall thickness in superior mesenteric artery and bilateral carotid arteries, she was diagnosed with Takayasu arteritis. It is emphasized that Fever of unknown origin and abdominal pain are atypical clinical manifestations of Takayasu arteritis, and early imagining including carotid doppler ultrasonography may help diagnosis of Takayasu arteritis in children.